Legal Education on the Urgency of Marriage Dispensation: A Review of Maṣlaḥah Mursalah and Positive Law - Saputro, Triyono Adi; Rahmawati, Awalia Rina; Ikhsan, Iqbal Nur Artianto (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
The current surge in requests for marriage dispensations among the public has attracted considerable interest in further examining the situation. This community service aims to provide insight and knowledge based on an analysis of the essence of marriage dispensations from an Islamic legal perspective. This activity was conducted online using the Zoom platform. This community service delivered legal dissemination by providing a review of court decisions regarding marriage dispensations for young men and women in the Karang Taruan community of Sidoharjo Village, Sragen. This community service material provides an analysis of the essence of dispensations granted for various reasons, such as premarital pregnancy, arranged marriages, and economic constraints. Dispensations have both positive impacts and negative impacts. In Islamic law, there is no specific age limit for marriage. The views of contemporary scholars vary. This research is expected to provide recommendations for Religious Courts to prioritize the interests of children, as well as the need for education on the negative impacts of early marriage as a provision and capital for children in the future, so as to minimize the risk of increasing early marriage and realize marriages that comply with religious law and state regulations. This community service activity has had a positive impact on youth Karang Taruna with a significant increase in the level of understanding and critical awareness of participants regarding the legal and sociological aspects and the negative impacts of disproportionate marriage dispensations.